Dampak perubahan jenis dan fungsi uang bagi perekonomian menurut perspektif ekonomi Islam - Asra Asra (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2020)
The alteration in the type and function of money which continue to roll creates a lot of new dynamics that are considered both positive and negative. In fact, this shift is influenced by many causes and reasons, this also affects the global economic problems. And it must be acknowledged that the issue of the type of money is the most crucial thing at the moment and continues to be debated on how to find solutions to the problem of paper money, especially related to inflation from the value of money itself. This paper tries to look out this issue, specifically from the perspective of the value of money (paper), where the value created is only based on perceptions or assumptions, not the value intrinsically attached to the medium of exchange itself, so it is very vulnerable to inflation.